On quality energy management in a third world country: the case study of war torn Libya - Khalil, Ashraf; Yaacob, Mashkuri; Khan, Sheroz; Aboadla, Ezzidin Hassan Elmabrouk; Tohtayong, Majdee; Aznan, Khairil Azhar (APBest Academy, Hong KOng, 2018)
The ever growing energy demands and the negative environmental impacts associated with global warming have pushed the policy makers toward adopting renewable energy sources. Unfortunately, the management of energy resources in many countries still fall short of optimizing the depleting nature of conventional energy sources and balancing them with untapped and abundant renewable energy sources. This calls for a detailed study on quality management of energy with the objective of minimizing losses and capitalizing on more efficient conversion methods of energy transfer for use in important industry applications. A good case study is in war torn country like Libya. Libya is one of the countries that recently struggles to satisfy its energy demand, although, the country has a high potential for solar energy. One major sector is electricity generation, which uses gas and fuel-fire to operate the turbines in the generation stations. Libya currently produces 33 TWH of energy to meet the demand of the local electricity market. The demand on energy will substantially increase in the near future as a result of economic development in order to build new infrastructure in Libya after the massive destruction that happened during the last four years. This will lead to more consumption of oil and gas, which causes a reduction in the national economical revenues, and more carbon dioxide emission. Therefore, Libya should use its alternative energy supplies to cover some of its load requirements. In this paper, we investigate the current energy situation in Libya while exploring the use of renewable energy to improve the current poor situation through some example scenarios. A quality management program of the energy landscape may be necessary as a way forward for the country to sustain any form of economic development amidst the shortage of energy resources in the country.